A New Index Proposal For Sustainable Cities - Turan Paksoy; Mustafa Atilla Arıcıoğlu; Büşra Yiğitol; Aylin Yılmaz Gezgin (Journal of Transportation and Logistics)
Sustainability can be defined as meeting today’s economic and social needs in such a way as to leave a livable environment for future generations without negatively impacting the ecosystem. Thus, one of the priorities today is to build cities and communities with sustainable living spaces. Such cities and communities are living spaces that meet the needs both of today and tomorrow in the most comprehensive and effective way. In this article, an index system is proposed to measure the sustainability of cities. The proposed sustainable city index was applied to Konya in Türkiye. The city was evaluated over three main dimensions and nine sub-dimensions. The annual increase and decrease of the index scores showed parallelism with the effects of the economic, technological, social and ecological events experienced in the last four years. The result of this study is of great importance as it shows the measurement reliability of the index. The sustainable city index can support recommendations that form the basis of policies and offer city-based performance scorecards for municipalities. It is recommended that city-based comparisons are made not only among cities in Türkiye but also worldwide in order to reach a better comparison.